Editorial: Australia’s National Artificial Intelligence Plan - Holmes, Jim; Campbell, Leith H (Journal of Telecommunications and the Digital Economy, 2025)
As with many countries in the world that are primarily technology takers, rather than technology leaders, Australia is seeking to address the issues for its place in the global digital ecosystem and to identify, and then realise, the opportunities that artificial intelligence (AI) may bring. On 2 December 2025, the Australian Government published its much-awaited National Artificial Intelligence Plan. In our editorial, we broadly summarise the Plan and discuss some initial reactions to it. We hope to revisit the subject in 2026 to find out how the Plan has fared at that stage. Also, we outline the eight technical papers published in this issue. In personnel changes, we note the resignation of the previous Editor-in-Chief.